Autismo em movimento : a mobilização da família no reconhecimento do autismo - Bianca Retes Carvalho (2022)
This dissertation proposes to analyze the care relations and political actions of family members of people on the autistic spectrum in the social and political recognition of autism and the realization of rights and public policies. The research was carried out through an ethnography in different networks of care and action in the city of Belo Horizonte/MG; among them, associations, municipal spaces and social networks. Interviews were also conducted with family members, autistic people and public agents; as well as participation in events and documentary analysis of rights and public policies related to autism. The trajectories of mothers and fathers of autistic individuals show how disability, kinship, care and the State are articulated in complex ways. Ethnography, therefore, based on theoretical discussions of kinship, social movements and care, makes it possible to reflect on how family relationships constitute and are constituted in the multiple meanings attributed to autism. Finally, this work points to the limits and possibilities of care practices that also conform to political practices, constituting democratic and participatory processes, in which the subjects’ experiences gain centrality to the demand for a more inclusive society.